ANALYTICAL TOOLS OF THE SEMANTIC FIELD IN MODERN GERMAN LANGUAGE: EVOLUTION, METHODS, AND APPLICATIONS (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The theory of semantic fields (Wortfeldtheorie), originating in German structuralist linguistics, continues to play a pivotal role in understanding lexical organization in modern German. This enhanced article surveys the historical foundations, core analytical tools, and contemporary advancements in semantic field analysis. Key tools include paradigmatic and syntagmatic relations, componential analysis, onomasiological and semasiological approaches, corpus-based distributional methods, and computational resources such as GermaNet. Integration with cognitive linguistics, frame semantics, and distributional semantics reflects a shift from rigid structuralist models to empirical, usage-based paradigms. Applications span lexicography, language teaching, diachronic studies, and natural language processing. Challenges like fuzzy boundaries and polysemy are addressed through hybrid methodologies, affirming the theory's enduring relevance in German lexical semantics.